Effect of a “pill mill” law on opioid prescribing and utilization: The case of Texas - Lyapustina, Tatyana; Rutkow, Lainie; Chang, Hsien-Yen; Daubresse, Matthew; Ramji, Alim F.; Faul, Mark; Stuart, Elizabeth A.; Alexander, G. Caleb (Drug and alcohol dependence, 2016)
•We model the impact of Texas’s 2010 ‘pill mill’ law.•We examine changes in morphine equivalent dose (MED), opioid volume, and number of prescriptions and pills.•We report significant declines in the outcomes examined.•Declines are concentrated among high-risk patients and prescribers. States have attempted to reduce prescription opioid abuse through strengthening the regulation of pain management clinics; however, the effect of such measures remains unclear. We quantified the impact of Texas’s September 2010 “pill mill” law on opioid prescribing and utilization. We used the IMS Health LRx LifeLink database to examine anonymized, patient-level pharmacy claims for a closed cohort of individuals filling prescription opioids in Texas between September 2009 and August 2011. Our primary outcomes were derived at a monthly level and included: (1) average morphine equivalent dose (MED) per transaction; (2) aggregate opioid volume; (3) number of opioid prescriptions; and (4) quantity of opioid pills dispensed. We compared observed values with the counterfactual, which we estimated from pre-intervention levels and trends. Texas’s pill mill law was associated with declines in average MED per transaction (−0.57mg/month, 95% confidence interval [CI] −1.09, −0.057), monthly opioid volume (−9.99kg/month, CI −12.86, −7.11), monthly number of opioid prescriptions (−12,200 prescriptions/month, CI −15,300, −9,150) and monthly quantity of opioid pills dispensed (−714,000 pills/month, CI −877,000, −550,000). These reductions reflected decreases of 8.1–24.3% across the outcomes at one year compared with the counterfactual, and they were concentrated among prescribers and patients with the highest opioid prescribing and utilization at baseline. Following the implementation of Texas’s 2010 pill mill law, there were clinically significant reductions in opioid dose, volume, prescriptions and pills dispensed within the state, which were limited to individuals with higher levels of baseline opioid prescribing and utilization.